DETERMINATION OF TOTAL FLAVONOID IN JAMU “X” WITH UV-VISIBLE SPECTROPHOTOMETRIC METHODS - Perdana Priya Haresmita; Missya Putri Kurnia Pradani (Universitas Muhammadiyah Magelang, 2022)
Jamu is still the choice of Indonesian people as an alternative to modern medicine until now. As a cultural heritage of the Indonesian, jamu is still very popular from the west to the east of Indonesia. The enthusiasm of the Indonesian in consuming jamu has encouraged many traditional medicine industries to produce jamu with many kinds of claim. Jamu